Lipopolysaccharide-Induced Autophagy Mediates Retinal Pigment Epithelium Cells Survival. Modulation by the Phospholipase D Pathway - Bermúdez, Vicente; Tenconi, Paula Estefanía; Giusto, Norma María; Mateos, Melina Valeria (Frontiers in Cellular Neuroscience, 2019)
Inflammation and oxidative stress are common factors involved in the pathogenesis of retinal diseases, such as aged-related macular degeneration and diabetic retinopathy. Autophagy is a catabolic process essential to cell survival in response to stress. This process is highly active in retinal pigment epithelium (RPE) cells. Our previous findings demonstrated that lipopolysaccharide (LPS) induces an inflammatory response of RPE cells that implies classical phospholipases D (PLD1 and 2) activation, cyclooxygenase-2 (COX-2) expression, prostaglandin E2 production and reduced cell viability. In this work we studied the autophagic process and its modulation by the PLD pathway in D407 and ARPE-19 RPE cells exposed to the LPS-induced inflammatory model. LPS (10 μg/ml or 25 μg/ml) exposure for 24 h increased LC3-II content (an autophagy marker) and LC3-positive punctate structures in both RPE cell lines studied. Next, the drug Bafilomycin A1 (BAF, 50 nM) was used to block the autophagic flux. In cells pre-incubated with BAF, LC3-II and sequestosome 1 (SQSTM1/p62) levels and autophagosome-like structures were increased by LPS, demonstrating that the inflammatory injury increases the autophagic process in RPE cells. To study the role of the PLD pathway, cells were pre-incubated for 1 h with selective PLD1 (VU0359595) or PLD2 (VU0285655-1) inhibitors prior to LPS addition. Under control condition LC3-positive punctate structures were increased in cells pre-incubated with PLD2 inhibitor while with PLD1 inhibitor they increased in cells exposed to LPS. MTT reduction assays showed that early autophagy inhibitors, 3-methyladenin (3-MA) and LY294002, enhanced the loss in cell viability induced by LPS exposure for 48 h. On the contrary, the inhibition of PLD1 and PLD2 prevented the loss in cell viability induced by LPS. In conclusion, our results show that even though LPS treatment promotes an inflammatory response in RPE cells, it also triggers the activation of the autophagic process which in turn may serve as a protective mechanism for the cells. In addition, we demonstrate that the PLD pathway modulates the autophagic process in RPE cells. Our findings contribute to the knowledge of the molecular basis of retinal inflammatory and degenerative diseases and open new avenues for potential therapeutic exploration.